Ensuring Adequate Early Childhood Development for Uganda’s Children - Kasirye, Ibrahim (Economic Policy Research Centre (EPRC), 2012)
Although Uganda has made significant progress in reducing child deaths in the past five years, the country still faces major challenges in ensuring adequate early childhood development. This briefing highlights some of the major challenges affecting children during the first five years of life with focus on: the low immunization coverage rates and vaccine availability; poor child nutritional health status; and the limited enrollment of children in Early Childhood Development Centres.